Urgensi Mekanisme Khusus dalam Penanganan Pelecehan Seksual di Transportasi Umum - Khanza, Shaffira Aura; Permanasari, Ai (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Sexual harassment on public transportation is a form of gender-based violence that remains prevalent in Indonesia. Although various regulations exist, such as Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, their implementation remains ineffective in providing protection and a sense of security for victims, particularly women. This study aims to analyze the mechanisms for handling sexual harassment on public transportation, identify the obstacles faced, and formulate solutions to strengthen legal protection for victims. The research method used is normative juridical, with a legislative and conceptual approach. Data were obtained through a literature review of laws and regulations, academic literature, and actual cases such as the harassment case on the Commuter Line (KRL) and Tanah Abang Station. The results show that the handling of sexual harassment cases on public transportation is suboptimal due to the absence of standardized SOPs, lack of coordination between agencies, and minimal officer sensitivity to victims. Furthermore, social stigma and patriarchal culture remain major barriers for victims to report. This study recommends the establishment of a comprehensive legal mechanism, including the development of integrated standard operating procedures (SOPs), the establishment of rapid response units in public transportation, regular training for officers, and strengthening a secure reporting system. This is expected to create a safe, equal, and sexual violence-free public space.